2002
DOI: 10.1677/joe.0.1750695
|View full text |Cite
|
Sign up to set email alerts
|

Drug-induced prevention of gastrectomy- and ovariectomy-induced osteopaenia in the young female rat

Abstract: Both ovariectomy (Ovx) and gastrectomy (Gx) induce osteopaenia in rats and humans. While the effect of Ovx has been ascribed to oestrogen deficiency, the underlying mechanism behind Gx is poorly understood. Alendronate, oestrogen and parathyroid hormone (PTH) are known to prevent the osteopaenia induced by Ovx in rats. The purpose of the present study was to determine whether alendronate, oestrogen or PTH could also prevent Gxevoked osteopaenia. Rats were Ovx-, Gx-, or were sham-operated (Sham) and were then t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
24
1
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 43 publications
7
24
1
3
Order By: Relevance
“…However, in the GX group, estrogen increased the trabecular BMD. Although estrogen had no significant effect in the SHAM-operated rats in this study, we have reported earlier that the same daily dose of estrogen increased the trabecular bone mass in SHAMoperated rats (Andersson et al 2002). Moreover, higher daily doses of estrogen have been shown to increase the trabecular bone mass in normal, intact rats (Wronski et al 1988).…”
Section: Discussioncontrasting
confidence: 56%
See 4 more Smart Citations
“…However, in the GX group, estrogen increased the trabecular BMD. Although estrogen had no significant effect in the SHAM-operated rats in this study, we have reported earlier that the same daily dose of estrogen increased the trabecular bone mass in SHAMoperated rats (Andersson et al 2002). Moreover, higher daily doses of estrogen have been shown to increase the trabecular bone mass in normal, intact rats (Wronski et al 1988).…”
Section: Discussioncontrasting
confidence: 56%
“…In an earlier study, we showed that OVXinduced osteopenia could be prevented by treatment with alendronate, estrogen or PTH. However, GX-induced bone loss can be prevented by giving alendronate, but not PTH or estrogen (Andersson et al 2002). Here we studied whether alendronate, estrogen or PTH is an effective treatment of established osteopenia induced by OVX or GX in rats.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations